Paraganglioma at the cerebellopontine angle: A case report and review of literature - Nadeem Akhtar; Fatimah Shahid; Alishba Shezal Ali; Qurat Ul Ain Muhammad; Noor Mahal Azam; Bishal Dhakal; Muhammad Ibrahim; Nehal Nadeem (Clinical Case Reports, 2024)
Key Clinical Message Paragangliomas (PGLs) are rare neuroendocrine tumors. Sometimes, these tumors secrete excessive catecholamines, which results in the manifestations of various signs and symptoms, usually with a triad of hypertension, tachycardia, and headache. We report the case of a 42‐year‐old woman presenting with uncontrolled hypertension, right facial palsy, vomiting, and disturbed gait. Diagnosis for PGL was confirmed on postoperative histological examination of the excised mass and correlated with preoperative clinical and radiological findings. Tumor excision was done via a suboccipital craniotomy approach. Our case presents the typically severe features of a jugulotympanic PGL, but most importantly, it highlights the necessity of biochemical diagnosing, thorough probing of the causes of hypertension, and a multi‐disciplinary approach in dealing with these tumors. Moreover, the case emphasizes necessitating the use of preoperative embolization in vascular tumors of the head and neck to avoid a hemorrhagic crisis during surgery. Unfortunately, due to a lack of adequate hospital funds, the surgeon had to proceed without preoperative embolization. Despite such a risk, the excision was a success.